The age of reconnaissance - Parry, J. H. 1914-1982 (World Publ. Co., 1963)
Age of Reconnaissance, as J. H. Parry has so aptly named it, was the period during which Europe discovered the rest of the world. It began with Henry the Navigator and the Portuguese voyages in the mid-fifteenth century and ended 250 years later when the "Reconnaissance" was all but complete. Dr. Parry examines the inducements--political, economic, religious--to overseas enterprises at the time, and analyzes the nature and problems of the various European settlements in the new lands